(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Hypertensive disorders are common complication occurring during pregnancy which are responsible for maternal and fetal mortality and morbidity. Objective: The purpose of the present study was to determine the perinatal outcome in pregnancy induced hypertension. Methodology: This study was designed as cross-sectional study and was conducted from April 2013 to September 2013 for a period of six (06) moths. Patients admitted in the Department of Obstetrics and Gynaecology at Shaheed Suhrawardy Medical College Hospital, Dhaka. Data were collected by interview, physical examintions (blood pressure, pulse rate, oedema, heart and lungs auscultation) and lab investigations using a structural questionnaire. Result: Majority of the women belonged to age group 21-25 year. Maximum were (56%) primigravida. The mean gestational age was 34.6 weeks with the range from 28 to 40 weeks. Hyperurecaemia was frequent among patients with pregnancy induced hypertension. Intrauterine growth retardation (IUGR) was secondary to pregnancy induced hypertension which was associated with significantly increased perinatal mortality. Conclusion: In this study, prematurity is frequent in pregnancy induced hypertension and convulsion in nonresponsive patients is associated with significantly increased perinatal mortality. Journal of National Institute of Neurosciences Bangladesh, January 2016;2(1): 10-13